OC-08 - Multiple functional defects in platelets from thrombocytopenic cancer patients undergoing chemotherapy. Issue 140 (April 2016) - Baaten, C.C.F.M.J.; Moenen, F.C.J.I.; Henskens, Y.M.C.; Swieringa, F.; Wetzels, R.; van Oerle, R.; ten Cate, H.; Beckers, E.A.M.; Heemskerk, J.W.M.; van der Meijden, P.E.J.
Abstract : Introduction: Severe thrombocytopenia (≤ 50 × 10 9 platelets/L) is often the consequence of hematological malignancies and intensive chemotherapy. The risk of clinically significant bleeding is increased in these patients, despite the use of prophylactic platelet transfusions. The fact that there is no clear correlation between the platelet count and the risk of hemorrhage, suggests that there are other contributing factors. The contribution of impairments in platelet and coagulant function remains poorly understood. Aim: In patients with chemotherapy-induced thrombocytopenia due to hematological malignancies, we evaluate platelet and coagulant functions and determine the effects of platelet transfusion. Ultimately, we can identify specific hemostatic factors that aid in the prediction of bleeding. Materials and Methods: In total 58 patients were included and blood was collected before and, if indicated (≤ 10 × 10 9 platelets/L), 1 hour after transfusion with platelet concentrate. Platelet function was assessed using flow cytometry by determining: 1) integrin αIIbβ3 activation (PAC-1 antibody), 2) P-selectin expression (anti-P-selectin antibody), 3) phosphatidylserine exposure (Annexin-V) and 4) intracellular calcium (Fluo-4 AM). Factor levels were determined in plasma. Thrombus and fibrin formation was assessed by perfusion of whole blood over a collagen-tissue factor surface at a shear rate of 1, 000 s-1. Results: Platelets from the thrombocytopenic patients before transfusion showed markedly reduced integrin αIIbβ3 activation and P-selectin expression in response to thrombin, collagen-related peptide and ADP, compared to healthy donor platelets. Also, agonist-induced intracellular calcium fluxes were greatly reduced. However, calcium fluxes with thapsigargin, a SERCA pump inhibitor, were similar in patient and control platelets, suggesting a normal calcium store content in the patient platelets. Furthermore, phosphatidylserine exposure was increased in unstimulated patient platelets compared to control platelets (8.2 vs. 1.8%, p < 0.0001). Coagulation factor levels were within the normal range, with the exception of von Willebrand factor and fibrinogen levels, which were elevated. Platelet transfusion partly recovered the platelet integrin αIIbβ3 activation and P-selectin expression induced by agonists. Platelet deposition (6.7 vs. 1.7%, p < 0.0001) and fibrin formation (7.6 vs. 0.9%, p = 0.0005) under flow conditions were substantially improved after platelet transfusion. Conclusions: Platelets from cancer patients undergoing chemotherapy appear to display impaired functional responses to activating stimuli. Platelet transfusion partly restores these functional defects, resulting in improved thrombus and fibrin formation.